Conference skills - Blake, Susan H. [ (Susan Heather)] , 1953-; Samwell-Smith, Rosemary; Soanes, Marcus (Blackstone bar manual, 2012)
Covering all aspects of a client interview in both civil and criminal proceedings, Conference Skills equips trainee barristers with the key case-work, written, and interpersonal skills required to conduct successful client conferences, and is fully supported by how-to-do-it guides, worked examples, and realistic case documentation